Patellar instability-induced bone loss in the femoral trochlea is associated with the activation of the JAK1/STAT3 signaling pathway in growing mice - Chen Ma; Wenguan Kou; Zhaoxia Cui; Wenfeng Liu; Changli Liu; Shengjie Wang; Fei Wang (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Introduction Patellar instability (PI) at an early age is believed closely correlated with bone loss in the development of the femoral trochlea and can cause trochlear dysplasia. However, the molecular mechanism of PI-induced bone loss has not been established. The Janus kinase (JAK)/signal transducers and activators of transcription (STAT) signaling pathway plays an important role in bone development by regulating the expression of osteoprotegerin (OPG) and receptor activator of nuclear factor kappa B ligand (RANKL). The aim of this study was to explore the association of JAK1/STAT3 signaling to PI-induced subchondral bone loss in the femoral trochlea. Methods Four-week-old male C57BL/6 mice were randomly divided into two groups (n = 50/group). Mice in the experimental group underwent surgery to induce PI. Distal femurs were collected 2 and 4 weeks after surgery (n = 25 knees/each time point, each group). Microcomputed tomography and histological observations were performed to investigate the morphology of the femoral trochlea and changes in bone mass. qPCR, western blot, and immunohistochemistry analyses were performed to evaluate the expression of JAK1, STAT3, RANKL, and OPG in subchondral bone. A t test was performed for the statistical analysis; a P value < 0.05 was considered to be statistically significant. Results In the experimental group, subchondral bone loss in the femoral trochlea was observed two and four weeks after PI; morphological changes, such as a flatter trochlear groove and an increased sulcus angle, were observed in the femoral trochlea; qPCR, western blot, and immunohistochemistry analyses showed higher expression of JAK1, STAT3, and RANKL and lower expression of OPG (P < 0.05). Conclusion PI-induced subchondral bone loss in the femoral trochlea and resulted in trochlear dysplasia in growing mice. This bone loss is associated with activation of the JAK1/STAT3 signaling pathway, which weakens the function of osteoblasts and stimulates both formation and function of osteoclasts.